Modeling the effect of weave structure and fabric thread density on the barrier effectiveness of woven surgical gowns. Issue 7 (2nd July 2016) - Maqsood, Muhammad; Nawab, Yasir; Hamdani, Syed Talha Ali; Shaker, Khubab; Umair, Muhammad; Ashraf, Waqas
Abstract : Surgical gowns are the shielding cloths worn by the surgical team throughout a surgery to save them from blood pathogens of the patient being operated, and to avoid bacterial infections. Barrier effectiveness of a fabric depends upon the liquid penetration resistance and pathogen resistance of the fabric. The objective of this study was to analyze the effect of different weave structures and fabric thread densities on the barrier effectiveness of the woven surgical gowns. Twelve fabric samples were produced using three different weave structures, i.e. 1/1 plain, 2/2 z-twill, and 3/3 z-twill, and four different fabric constructions and then completed with a water repellent finish. Water repellency spray test and air permeability test were conducted on each of the 12 woven samples. The results of fabric samples were analyzed in Minitab statistical software. The coefficients of determinations ( R 2 values) of the regression equations show good prediction ability of the developed statistical models. The findings of the study may be helpful in deciding appropriate manufacturing specifications of surgical gowns to attain maximum barrier effectiveness.